The influence of ionic liquids cation on the properties of sulfonated poly (ether ether ketone)/polybenzimidazole blends applied in PEMFC - da Trindade, Letícia G. [UNESP]; Zanchet, Letícia; Martins, Pedro C.; Borba, Katiúscia M.N.; Santos, Rapher D.M.; Paiva, Robert da S.; Vermeersch, Lilian A.F.; Ticianelli, Edson A.; de Souza, Michèle O.; Martini, Emilse M.A. (Elsevier, 2019)
Blends modified with ionic liquid (IL) can have their conductivity improved at elevated temperatures and low relative humidity (RH) making them suitable for proton exchange membrane fuel cells (PEMFCs) applications. This study explores the synthesis and characterization of sulfonated poly (ether ether ketone)/polybenzimidazole/3-triethylammonium hydrogen sulfate (TEA-PS.HSO4) or 1-butylimidazole hydrogen sulfate (BImH.HSO4) ionic liquids blends to be applied as a novel proton exchange membranes (PEM). The oxidative stability augments with the increase of PBI content, and the membrane conductivity enhances with the increase of the IL content. Additionally, the H bond formed between the acid proton of the IL cation and the amine group of PBI avoids the IL leaching. In the PEMFC applications, the best results were obtained using the SP10/TEA5 membrane (10 and 5 wt% of PBI and TEA-PS.HSO4 respectively) at 100 °C. A high Open Circuit Potential (OCP) value was achieved (0.97 V) and an increase of 126% of the density current (1.83 A cm−2) when compared with a pure SPEEK membrane (0.81 A cm−2). These results indicate that these composite membranes have a high potential for PEMFC applications.
Keywords: Ionic liquid; Polybenzimidazole; Proton exchange membrane fuel cell; Sulfonated poly (ether ether ketone)